PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP HASIL BELAJAR DASAR LISTRIK DAN ELEKTRONIKA KELAS X TEKNIK ELEKTRONIKA SMK NEGERI 1 BUKITTINGGI - Siti Maisyarah Arza; Nelda Azhar; Ika Parma Dewi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
This study aims to determine the influence of cooperative learning model two stay two stray learning outcomes in electrical and electronics elementary subjects of x class students majoring in electronics engineering at SMK Negeri 1 Bukittinggi. This type of research is an experimental with intact group comparison design.The research sample is class X TE 2A as experiment class using cooperative learning model Two Stay Two Stray and class X TE 2B as control class using Problem Based Learning model. Technique of collecting data from post-test every meeting in experiment class and control class, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results obtained an average value of 81,13 while the control class get an average value of 74,06. The result of hypothesis calculation at significant level α = 0,05 got tcount> ttable that is 2,996> 1,697, because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. Can be concluded means at the real level, this study shows that, there is influence of positive learning outcomes between the use of cooperative learning model type Two Stay Two Stray with the model of Problem Based Learning in Electrical and Electronics Elementary students X class students majoring in electronics  engineering at SMK Negeri 1 Bukittinggi. So the results of student learning Two Stay Two Stray  can increase the learning outcomes of students and made student more active on study.Keywords: Learning Outcomes , Two Stay Two Stray (TSTS), Poblem Based Learning (PBL).